Lunette Vaults in Guarini’s Work. Digital Models between Architettura Civile and Modo di Misurare le Fabriche (diségno, 2019)
In Guarini’s systematization of vaulted systems based on geometric reasoning, the lunette vaults created by cutting main vaults of different geometric shape and inserting the groins take on a primary role. This operation increases the natural lighting of the rooms and ensures airiness and dynamism to atria and halls of Baroque palaces. In the Architettura Civile (published posthumous in 1737) and the Modo di misurare le fabriche (1674), he describes the geometrical origin and the measurement of the vaults, respectively. In the first treatise, the lunette vaults emerge as a typology rich of shape variations and implementations in civil buildings, in the second the surfaces of the vaults are attributed to the geometric matrices of the single elements and present some novelties with respect to the Architettura Civile, having semi-ellipses, and arcs of circumference and ellipse, as directrices. In this work the significant relationships between these two Guarini’s treatises, whose complementarity emerges in the continuous reference to the Geometry-Architecture binomial, are developed and deepened. The graphical analysis and digital modeling of surfaces allow not only the recognition of the geometric primitives underlying the structure of the vaulted systems and the verification of the measurement rules that Guarini largely attributes to himself, but also the comparison with the architectures realized in the period of the second expansion of Turin.
Keywords: graphical analysis; digital modeling; lunettes; lunette vaults; treatises; Guarini